Analysis of Patient's Return Visit at Government Public Hospital in Lampung Province - Febriansyah; Wibowo; Sitinjak, Tony (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
A government public hospital is a public facility owned by the government that has a very strategic role in efforts to improve public health services. The new health service paradigm requires the hospital to provide quality services according to the needs and desires of patients while still referring to the professional and medical code of ethics. With technological developments rapidly and competition increasingly fierce, hospitals are required to improve the quality of their services. Quality is the core of the continuity of life of an institution. Therefore, hospitals are required to always maintain their image and consumer trust by improving service quality to ensure satisfaction Consumers increase which will ultimately increase interest in repeat visits to patients. This research aims to analyze the influence of service quality and image of hospitals and trust in intention to revisit through satisfaction mediation patients at four Government General Hospitals in Lampung Province. Method The research used in this research is a survey method. Technique Data collection uses observation, interviews, and questionnaires. Results research shows that 53% of the total variation in the repeat visit interest variable can be explained by the variables of service quality, hospital image, and trust, the remaining 47% is explained by other variables not used in the research. Apart from that, it can be identified that the dominant factors that drive the patient to make repeat visits to government RSUs in Lampung Province, namely the hospital provides services as promised, services that are provided immediately to customers, hospital service capabilities, hospital medical costs can be installments, as well as the cleanliness and tidiness of the treatment room. Other factors, namely service immediate service to customers, state-of-the-art medical equipment, and nursing care to sit, stand, and walk